Acetaminophen for all-out power output: Same pain, some gain - Koziris, L. (Strength and Conditioning Journal, 2014)
A recent study demonstrated that in a set of cycling intervals, acetaminophen did not affect pacing strategy in earlier sprints but permitted higher power output in later sprints. The effect of acetaminophen on pain sensation likely enabled a higher exertion level within the same perceived pain level. Special caution should be exercised in recommending any analgesic.